FOBIA SOCIAL EN LOS ESTUDIANTES DE PRIMER SEMESTRE DE LA CARRERA DE PSICOPEDAGOGIA DE LA UNIVERSIDAD NACIONAL DE CHIMBORAZO, PERIODO 2018-2019 - Martínez Coca, Karen Monserrath (2020)
The objective of this research was to identify social phobia level in first semester students, at Psycho pedagogy major of the National University of Chimborazo, from 2018 to 2019. Social phobia is a persistent and irrational fear about situations that may involve observation and judgment by others such social or speaking in public. The fear may start in adolescence or becaused by overprotective parents or by limited social opportunities. People who suffer from social phobia are at high risk of consuming alcohol or other drugs. The reason is that they trust those substances in other to relax in social situations. Methodologically it was worked with a non-experimental design. The type of research is field, bibliographic, transversal, descriptive and correlational. The sample was an intentional non-probabilistic type established in 34 students as participants. It including 11 men and 23 women. The instrument for data collection was a psychometric test. The technique was an anxiety scalr for social interaction (SIAS-20) by Mattick and Clarke, as part of the independent variable. It can be concluded that women have greater social phobia than men; knowing that this phobia is on a medium scale. However, women can become more spontaneous to participate in classroom through therapy. It may not only help them become more confident, but also to express their thoughts without any embarrassment feeling.